EXAMINATION OF NARCISSISTIC AND MACHIAVELLIAN CHARACTER TRAITS IN LEADERS - Szanto, Gerda (Applied Studies in Agribusiness and Commerce, 2023)
The leader is a person of essential importance in the life of an organization. Someone who can keep things in order. All of this is a very diverse task that requires countless skills, which affects the organizational culture, the success of the company, the satisfaction and efficiency of the employees. The objective of my research is to examine whether narcissistic and Machiavellian traits appear in individuals with leadership experience, and how they feel about the issue of empowerment and certain assertive situations. The sample of my research was 102 leaders. I made sure that there is a correlation between the mentioned variables.